1919
DOI: 10.1016/s0140-6736(01)48604-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigations ON THE NORMAL VITAL CAPACITY IN MAN AND ITS RELATION TO THE SIZE OF THE BODY.

Abstract: DURING the last few years questions relating to the vital-capacity of man have acquired prominent importance, since this measurement has been a decisive factor in the selection .,or exclusion of candidates for our Flying Service. A definite minimum standard of " vital capacity" was fixed, more or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1920
1920
1972
1972

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 2 publications
2
12
0
Order By: Relevance
“…The correlation matrix for all data is presented in Table 2. The data generally agreed with that reported by other investigators (Dreyer, 1919;Hewlett and Jackson, 1922;Cureton, 1936;Costill, 1967;Adams, 1968). Seven subjects were track athletes, six participated in other forms of athletics, and 11 were untrained students.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The correlation matrix for all data is presented in Table 2. The data generally agreed with that reported by other investigators (Dreyer, 1919;Hewlett and Jackson, 1922;Cureton, 1936;Costill, 1967;Adams, 1968). Seven subjects were track athletes, six participated in other forms of athletics, and 11 were untrained students.…”
Section: Resultssupporting
confidence: 91%
“…Contraindicatively, Dreyer (1919) found that weight exhibited the most consistent relationship with vital capacity. Hewlett and Jackson (1922) found the correlations of vital capacity with weight and with height to be approximately equal.…”
Section: Review Of Literaturementioning
confidence: 97%
See 1 more Smart Citation
“…These findings were, in general, in good agreement with those of Emerson and Green (1921), Needham, Rogan, and McDonald (1954), West (1920), and Dreyer (1919).…”
Section: Resultssupporting
confidence: 89%
“…Further differences in procedure on individual measures are as follows: For length* of the stem in the erect posture the child sat in the stadiometer, with its spine in contact with the stadiometer, and knees flexed by placing its feet up on the platform in the position described by Dreyer (17). The experimenter then held the head in place and measured in the same way as for standing length.…”
Section: The Present Studymentioning
confidence: 99%